Discovery of the membrane receptor for mitochondrial fission GTPase Drp1 - Otera, Hidenori (Landes Bioscience, 2011)
Mitochondria frequently change their morphology by fusion and fission, and these dynamic morphologic changes are essential for maintaining both mitochondrial and cellular functions. The cytoplasmic dynamin-related guanosine triphosphatase (GTPase) Drp1 (Dnm1 in yeast) is recruited to mitochondrial fission sites and severs mitochondria. Although the mitochondrial outer membrane (MOM) protein Fis1 functions as a membrane receptor for Dnm1 in yeast, it is not yet known whether the human homolog of yeast Fis1 (hFis1) is a membrane receptor for Drp1 in mammals. We recently identified the C-tail anchored MOM protein Mff as the bona fide receptor essential for recruiting Drp1 to mitochondrial fission sites. Here, we focus on this key molecule for mitochondrial fission after a brief description of the proteins involved in mitochondrial fission and fusion reactions. Finally, we discuss the expected role of hFis1 for regulating the mitochondrial dynamics in mammals.